RELEVANSI PENDEKATAN TEKSTUAL DAN KONTEKSTUAL (STUDI KOMPARATIF DALAM MEMAHAMI PESAN AL-QUR’AN) - Samsir, Samsir; Salewe, M Idman; Tahir, Tarmizi (TAFASIR: Journal of Quranic Studies, 2025)
This study examines the relevance of textual and contextual approaches in understanding the message of the Qur’an through a comparative study. The textual approach emphasizes the literal meaning and linguistic structure of the verses, while the contextual approach considers the historical, social, and cultural dimensions surrounding the revelation. Using a qualitative method based on literature review, this study analyzes primary and secondary sources relevant to Qur’anic exegesis. The findings indicate that the contextual approach offers a more responsive understanding of contemporary issues, whereas the textual approach is essential to preserve the integrity and purity of the Qur’anic message. The integration of both approaches is proposed as an ideal model for interpreting the Qur’an comprehensively and contextually. This article contributes to the development of Qur’anic exegesis methodology that is adaptive to modern social dynamics.Keywords: Qur’anic Interpretation; Textual Approach; Contextual Approach; Comparative Study